Is assigning a descriptor with definitive functional or clinical annotation to molecules or signaling pathways a hindrance to advancements in biomedical research? / Julie Y.H. Chan and Samuel H.H. Chan - Chan, Julie Y.H; Chan, Samuel H.H (Faculty of Medicine, 2023)
A common practice in contemporary biomedicine is to assign a descriptor with definitive functional or clinical annotation to a particular molecule or signaling pathway. Thus, terms such as tumor suppressor molecules or survival signaling pathways abound in the literature. Despite its simplicity and convenience, this practice may not be a true reflection of how human bodies function. This is because manifestations of body functions represent the outcomes of orchestrated events that are integrated at multiple levels of systems, organs, tissues, cells, and molecules. When these multilevel integrations are executed in "good" rapport, our body functions are operated in the "physiological" zone. "Pathophysiological" conditions will be instigated when they turn into "bad" relationships, leading to the development of diseases. The "ugly" scenario will emerge on the breakdown of the multilevel integration system, which prompts "pathological" states that head for fatality.